Two glutamine synthetase genes from Phaseolus vulgaris L. display contrasting developmental and spatial patterns of expression in transgenic Lotus corniculatus plants. - Forde, B G (1989)
The gln-gamma gene, which specifies the gamma subunit of glutamine synthetase in Phaseolus vulgaris L., has been isolated and the regulatory properties of its promoter region analyzed in transgenic Lotus corniculatus plants. A 2-kilobase fragment from the 5'-flanking region of gln-gamma conferred a strongly nodule-enhanced pattern of expression on the beta-glucuronidase reporter gene. Parallel studies on the promoter of another glutamine synthetase gene (gln-beta) showed that a 1.7-kilobase fragment directed 20-fold to 140-fold higher levels of beta-glucuronidase expression in roots than in shoots. Histochemical localization of beta-glucuronidase activity in nodules of the transgenic plants indicated that the chimeric gln-gamma gene was expressed specifically in the rhizobially infected cells; expression of the gln-beta construct was detected in both cortical and infected regions of young nodules, and became restricted to the vascular tissue as the nodule matured. We conclude that gln-beta and gln-gamma genes are differentially expressed both temporally and spatially in plant development and that the cis-acting regulatory elements responsible for conferring these contrasting expression patterns are located within a 2-kilobase region upstream of their coding sequences.